Role of the Immunohistochemical Marker (Ki67) in Diagnosis and Classification of Hydatidiform Mole - Deka FF, Hasan Abu; ZH, Abd Ali Al Saeng; Z, Khalid Almukhtar (IIUM Medical Journal Malaysia, 2019)
Introduction: Since the hallmark of gestational trophoblastic disease is trophoblastic proliferation, Ki67 is regarded as the best marker in studying hydatidiform mole.This study was conducted to evaluate the role of this proliferative marker in distinguishing among hydropic abortion, partial and complete hydatidiform mole. Materials and methods: This is a cross sectional study involving the application of Ki67 on a total of 90 histological samples of curetting materials from molar (partial and complete mole) and non molar hydropic abortion belong to Iraqi females, so three study groups were created. Immunohistochemical expression in villous cytotrophoblasts, syncytiotrophoblasts and stromal cells were recorded separately by three independent observers and the results were correlated statically. Results: The mean number of stained nuclei of villous cytotrophoblasts and stromal cells was the highest in complete mole and the lowest in non molar hydropic abortion. There is a significant statistical relationship regarding Ki67 labeling index in villous cytotrophoblasts between partial moles and hydropic abortion, complete mole and partial moles, hydropic abortion and complete mole. Regarding Ki67 labelling index in villous stromal cells, a significant statistical relationship achieved when the correlation done between partial mole and hydropic abortions, hydropic abortion and complete mole, while a non significant statistical relationship was achieved if the correlation done between partial and complete mole. All villous syncytiotrophoblasts showed negative results. Conclusion: Ki-67 labeling index in villous cytotrophblastic cells are useful in separating between partial moles and hydropic abortion, partial mole and complete mole, hydropic abortion and complete mole. While Ki-67 labeling index in villous stromal cells is only useful in separating between partial moles and hydropic abortion, hydropic abortion and complete mole.